2016
DOI: 10.1155/2016/1251637
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of Echocardiography in Syncope Patients with Normal ECG

Abstract: Aim. This study aimed to assess the role of echocardiography as a diagnostic tool in evaluating syncope patients with normal versus abnormal electrocardiogram. Methods. We conducted a retrospective study of 468 patients who were admitted with syncope in 2011 at St. Joseph's Regional Medical Center, Paterson, NJ. Hospital records and patient charts, including initial emergency room history and physical, were carefully reviewed. Patients were separated into normal versus abnormal electrocardiogram groups and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Furthermore, as previously mentioned, the absolute number of patients undergoing echocardiography has decreased due to the favorable trends in hospitalization rates. Finally, we did not find a statistically significant reduction in in‐hospital mortality among those receiving an echocardiogram thus supporting the low diagnostic yield of echocardiogram demonstrated in previous studies . While the reasons for its increased utilization in our study need further exploration, it is most likely a result of increased comorbidities and cannot be attributed to inappropriate use.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Furthermore, as previously mentioned, the absolute number of patients undergoing echocardiography has decreased due to the favorable trends in hospitalization rates. Finally, we did not find a statistically significant reduction in in‐hospital mortality among those receiving an echocardiogram thus supporting the low diagnostic yield of echocardiogram demonstrated in previous studies . While the reasons for its increased utilization in our study need further exploration, it is most likely a result of increased comorbidities and cannot be attributed to inappropriate use.…”
Section: Discussionsupporting
confidence: 70%
“…Prior research from the late nineties has suggested that routine echocardiogram use in unselected patients with syncope was common and was ordered in two‐thirds of patients presenting with syncope . However, subsequent investigations have demonstrated that echocardiographic abnormalities that impact treatment decisions are uncommon in unselected patients with syncope, particularly in those with a benign cardiac examination, normal ECG, and without pre‐existing cardiac disease . The current ACC/AHA/HRS guidelines recommend against the routine use of cardiac imaging in the evaluation of patients with syncope unless cardiac etiology is suspected on the basis of an initial evaluation, including history, physical examination, or ECG .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formal echocardiography is frequently used to stratify risk, particularly in elderly patients with a history of cardiac disease, an abnormal ECG or unexplained recent‐onset syncope . We accept that, when the cardiovascular exam is normal, the positive diagnostic rate of formal echo is low . However many of our patients had abnormal physical signs that were confirmed or ruled out by PBU, thus speeding up the decision‐making process as to whether further investigations were required in or out of hospital .…”
Section: Discussionmentioning
confidence: 88%
“…5 We accept that, when the cardiovascular exam is normal, the positive diagnostic rate of formal echo is low. 6 However many of our patients had abnormal physical signs that were confirmed or ruled out by PBU, thus speeding up the decision-making process as to whether further investigations were required in or out of hospital. 7 With regard to heart failure, left ventricular function cannot reliably be estimated from physical examination, but both systolic and diastolic dysfunction can be rapidly diagnosed by PBU.…”
Section: Brief Communicationsmentioning
confidence: 95%